ANALISIS FAKTOR YANG MEMPENGARUHI EFEKTIVITAS IKLAN ONLINE DI BUKALAPAK MENGGUNAKAN MODEL AIDA(Studi Kasus pada Pengguna Aplikasi Bukalapak di Kota Bogor) - Muhamad Fajar Awaludin (2020)
This study aims to determine the factors from the AIDA model (Attention, Interests, Desires, Actions) that influence effectiveness of online advertising, and to find out the factors that become dominant factors on the effectiveness of online advertising. This research was conducted on 140 people who had made a purchase transaction through the Bukalapak using factor analysis. Results showed that the factors that influence the effectiveness of online advertising from AIDA model consist of 14 variabels whice are formed intu four new factors. The first factor that is determinnant factor the forming factors consist of attention to the title or the title of the ad, understand the advertising message, see reviews and ratings, put the product in the shopping basket, choose the payment method, and make a purchase transaction. forming factors consist of interest in finding information about the product, interest in reading product descriptions, and looking at the product catalog. The third factor is desire (desire) with the forming factors consisting of buyers, the desire to buy products, and purchases to purchase,and attention (attention) consists from attention to images or photos, and attention to messages or supporting information.